2006
DOI: 10.1159/000095808
|View full text |Cite
|
Sign up to set email alerts
|

Attention Problems among Children with a Positive Family History of Alcohol Abuse or Dependence and Controls

Abstract: This longitudinal study investigated the scope and course of attention problems over a period of time from preteen (ages 7–12 years) to early teen years (ages 13–17 years). We compared symptoms in subjects with and without a family history (FH) of alcohol abuse or dependence from among families without evidence of antisocial personality disorder. Evaluations of attention problems for the offspring were based on the Child Behavior Checklist and a validated semistructured interview carried out with the mother. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…That said, better measurements of the relationship of cognitive impairment to later alcoholism are made by family history and longitudinal studies. One study that tested family history positive teens found no impairment on attentional measures (Barnow et al., 2007), but when multigenerational or higher familial alcoholism density are used as factors, attentional impairment can be detected (Corral et al., 1999, 2003). An 8‐year longitudinal study with high‐risk youths found that attentional impairment/executive functioning predicted later substance use, even when controlling for intake substance involvement, gender, education, conduct disorder, family history, and learning disabilities (Tapert et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…That said, better measurements of the relationship of cognitive impairment to later alcoholism are made by family history and longitudinal studies. One study that tested family history positive teens found no impairment on attentional measures (Barnow et al., 2007), but when multigenerational or higher familial alcoholism density are used as factors, attentional impairment can be detected (Corral et al., 1999, 2003). An 8‐year longitudinal study with high‐risk youths found that attentional impairment/executive functioning predicted later substance use, even when controlling for intake substance involvement, gender, education, conduct disorder, family history, and learning disabilities (Tapert et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about the manner in which attributes such as BU contribute to alcohol-related problems in groups with higher education, higher income and who were not selected for pre-existing problems [29,44,45]. Because the lifetime risk for more extreme disorders such as CD and ASPD in males is estimated to be less than 5%, and only 20% of male alcoholics entering treatment fulfill criteria for ASPD [46,47], it is important to establish whether a characteristic such as BU still contributes to the AUD risk in less deviant groups who may be more representative of non-treated populations.…”
Section: Introductionmentioning
confidence: 99%
“…While there is little doubt regarding the importance of externalising characteristics such as BU to the pattern of heavier drinking and associated problems, most studies of these relationships have been carried out in adolescents and populations chosen at least in part for deviant behaviours [42,43]. Less is known about the manner in which attributes such as BU contribute to alcohol-related problems in groups with higher education, higher income and who were not selected for pre-existing problems [29,44,45]. Because the lifetime risk for more extreme disorders such as CD and ASPD in males is estimated to be less than 5%, and only 20% of male alcoholics entering treatment fulfill criteria for ASPD [46,47], it is important to establish whether a characteristic such as BU still contributes to the AUD risk in less deviant groups who may be more representative of non-treated populations.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning ADHD, earlier work defines it as narrow DSM-IV ADHD (Knopik et al, 2006), ‘any ADHD,’ symptom count, and ADHD with or without clinical impairment (Knopik et al, 2005). Considering the larger literature, other definitions such as dimensions of ADHD (Barnow et al, 2007), laboratory tasks (Corral et al, 1999), behavioral undercontrol (Sher, 1991), and attention and memory deficits (Tarter et al, 1989) have been used. Further, even when parental alcoholism has been found to predict ADHD, non-genetic and genetic explanations have often been difficult to untangle from one another since most studies in this literature have not used genetically informative design (Knopik et al, 2006).…”
Section: Discussionmentioning
confidence: 99%